Republic of the Marshall Islands : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper discusses correspondent banking relationships (CBRs) pressures on the Republic of the Marshall Island (RMI). RMI's two banks currently have access to the US financial system. The Bank of the Marshall Islands is a domestic financial institution providing banking services to a substantial portion of the population and operates five branches throughout RMI, including on the Kwajalein Atoll. RMI, through the Trust Company of the Marshall Islands, provides offshore corporate and maritime registry services. Weak implementation of the anti-money laundering and combating the financing of terrorism (AML/CFT) framework by the authorities contributes to CBR pressures in RMI. The termination of BOMI's CBR with First Hawaiian Bank would be expected to have significant negative economic repercussions without alternative arrangements. The RMI authorities are strengthening the effectiveness of the AML/CFT framework. Additional steps should be taken to further lower the risk of losing the last US dollar CBR. Once the national risk assessment is completed, an action plan should be developed to address the identified risks.